Decoding the molecular pathways governing trophoblast migration and placental development; a literature review - Liu, Lianlian; Tang, Lin; Chen, Shuai; Zheng, Lianwen; Ma, Xiaoyan (Frontiers in Endocrinology, 2024)
Placental development is a multifaceted process critical for a fruitful pregnancy, reinforced by a complex network of molecular pathways that synchronize trophoblast migration, differentiation, and overall placental function. This review provides an in-depth analysis of the key signaling pathways, such as Wnt, Notch, TGF-β, and VEGF, which play fundamental roles in trophoblast proliferation, invasion, and the complicated process of placental vascular development. For instance, the Wnt signaling pathway is essential to balance trophoblast stem cell proliferation and differentiation, while Notch signaling stimulates cell fate decisions and invasive behavior. TGF-β signaling plays a critical role in trophoblast invasion and differentiation, predominantly in response to the low oxygen environment of early pregnancy, regulated by hypoxia-inducible factors (HIFs). These factors promote trophoblast adaptation, ensure proper placental attachment and vascularization, and facilitate adequate fetal-maternal exchange. Further, we explore the epigenetic and post-transcriptional regulatory mechanisms that regulate trophoblast function, including DNA methylation and the contribution of noncoding RNAs, which contribute to the fine-tuning of gene expression during placental development. Dysregulation of these pathways is associated with severe pregnancy complications, such as preeclampsia, intrauterine growth restriction, and recurrent miscarriage, emphasizing the critical need for targeted therapeutic strategies. Finally, emerging technologies like trophoblast organoids, single-cell RNA sequencing, and placenta-on-chip models are discussed as innovative tools that hold promise for advancing our understanding of placental biology and developing novel interventions to improve pregnancy outcomes. This review emphasizes the importance of understanding these molecular mechanisms to better address placental dysfunctions and associated pregnancy disorders.